Rancang Bangun Sistem Arsip Surat Kerja Sama Daerah berbasis Web dan Android di Pemkot Singkawang - Rr. Hajar Puji Sejati; Teofilus Figo Ananda Nicolas (G-Tech: Jurnal Teknologi Terapan, 2024)
The government sector is expected to utilize technology to support and optimize their respective performances, enabling them to provide better services to the public. The ‘Regional Cooperation Letter Archive System’ is developed to support the performance of the Singkawang City government in terms of archiving cooperation letters, which are currently conducted using paper-based and traditional methods. The development of this system utilizes the Rapid Application Development (RAD) method, going through several phases of data collection. This research includes interviews with the Secretariat of Singkawang City to gather information about archiving incoming and outgoing letters using the old methods. Because of the existence of this application that utilizes an online database, administrators do not need to spend time storing or accessing old incoming and outgoing letters. Administrators will also be evident when offering collaborations with other institutions or organizations.